Boom town - Stone, Nic (Simon & Schuster, 2025)
When Damaris "Charm" Wilburn, a new daytime dancer, is missing for her shift at Boom Town, former headliner Mihah "Lyriq" Johanssen suspects something more than a "no call, no show." As Lyriq's former headline partner and lover--Felice "Lucky" Carothers--also vanished under similar circumstances, Lyriq decides she's going to find them. Delving deeper into Charm and Lucky's disappearances, Lyriq uncovers a tangled web of deceit, privilege, and power. The line between friend and foe blurs, forcing Lyriq to confront the question: Is finding for these women worth the threat to her own life? This tantalizing thriller will take you on a heart-pounding and page turning journey through the peaks and valleys of Atlanta's underworld.